Pengaruh Iklim Organisasi dan Kompetensi terhadap Kinerja Pegawai pada Kantor Dinas Perhubungan Provinsi Aceh - Filia Hanum (JABE (Journal of Applied Business and Economic), 2018)
This study aims to determine the effect of organizational climate and competence on employee performance at the Aceh Transportation Service office. The results of the study simultaneously that the organizational climate and competence have a significant effect on employee performance, because the calculated F count  is greater than the value of F table , then Ha = accepted and Ho = rejected. Then partially each organizational climate variable and competency variable have a significant effect on employee performance, because each variable has a t count  greater than t table , Ha = accepted and Ho = rejected. Furthermore, the value of the correlation coefficient (R) shows a value of 0.596 which indicates that the relationship between the independent variable and the dependent variable is positive.